(untitled) (Ustozlar uchun, 2026)
The recurrent approach is an integrated approach that is a synthesis of existing studies of cyclical processes in the study of modern macroeconomic processes, taking into account the nature of their intercyclic and interphase dependencies. Based on its main provisions, the digital economy is a natural phase of depression (an interphase transition from a neo-industrial to an information-innovative economy) within the framework of the modern transformation cycle. The recognition of the depression phase significance in the phase structure allowed us to assert that the digital economy is two-fold in nature, it intertwines the processes characteristic of the neo-industrial economy, and also forms processes that provide a “breakthrough” to the information-innovative economy. In other words, it is formed under the influence of the completeness of neo-industrial processes, implying increased digitalization. However it also becomes the basis for the formation and development of different forms of economic development within the post-industrial cycle.